Sousveillance as an Ambiguous Practice of Negotiating In/Visibility: The Case of Forensic Architecture - Godarzani-Bakhtiari, Mina (Surveillance & Society, 2026)
Hardly anywhere are the consequences of data invisibility more life-threatening than at national borders, creating a vicious cycle of surveillance, violence, and death. Sousveillance initiatives challenge this by making violence visible. While their work aims to educate the public about state violence, the complex relationship between sousveillance and visibility needs further exploration. Sousveillance claims to be a communicative act of resistance; assessing this claim requires examining how visibility is produced and what form it assumes. The work of Forensic Architecture (FA), a sousveillance research agency, is fruitful for this, as its investigative videos aim to show how evidence is made. Using comparative video artefact analysis to examine a video in which FA presents its reconstruction of the 2020 shooting of a Syrian refugee at the Turkish-Greek border, this study details the complex, sequential process of producing visibility of violence as evidence. I will show that FA conducts a culturally specific form of analysis in which data interpreting and synthesizing information are carried out by establishing an abstract understanding of space. The visibility produced by FA is inherently ambiguous: It de- and re-subjectivizes, abstracts from social difference, and differentiates the subjects in question. These ambiguities highlight the challenges of negotiating data in/visibility and provide new insights into debates on sousveillance as resistance in the context of state violence.